ANALISIS PENGARUH KUALITAS LAYANAN DAN CITRA TERHADAP KEPUASAN DAN DAMPAKNYA PADA LOYALITAS INVESTOR DI PT.VALBUR (ASIA FUTURES (Studi Pada PT. Valbury Asia Futures Semarang) (Students' Journal of Economic and Management, 2014)
The study entitled " Analysis of Quality Service and Image for Satisfaction Investors and its impact on Loyality PT. Valbury Asia Futures" . It examines the problem of not reaching the target consumer satisfaction and dissatisfaction to the attention of investors increasingly companies in developing service strategies , so that customer satisfaction is placed as the primary goal of customer satisfaction according to company creation Tjiptono (2005 ) may provide some benefits among which the relationship between companies and investors become harmonious, be a good base for the use of repeat purchases (repeated buying) , the creation of customer loyalty (customer loyalty) that is profitable for the company . This study aims to identify and analyze whether there is a variable effect corporate image , and quality of service to the satisfaction of investors and its impact on investors loyaliyas PT.Valbury Asia Futures Semarang . Criteria samples obtained a number of 68 investors . The analysis used is the analysis of the validity , reliability and multiple linear regression. Addressing the validity of the test results to be stated that all the indicators are valid for all known variables can be addressed reliability test that all the instruments reliable . Based on the results of the regression analysis can be seen that the image and service quality has a positive effect on investor satisfaction and Loyalty have positive impact in improving Keywords: corporate image, service quality, customer satisfaction and loyality